Prestasi Belajar pada Remaja yang Mengalami Dismenorea Primer - Fajarini, Yuniar Ika; Nurdiati, Detty Siti; Padmawati, Retna Siwi (JURNAL KESEHATAN REPRODUKSI, 2018)
Background: Primary dysmenorrhea occurs in approximately 50% of teenage girls and cause serious disruptions in the quality of life and daily activities. Primary dysmenorrhea makes teenagers difficult to concentrate in school which will decrease their academic achievement.Objective: to investigate whether there is a correlation between Primary dysmenorrhea and academic achievement of students of SMP Islam Terpadu Pondok Pesantren Tahfidzul Qur’an (SMP IT PPTQ) Ibnu Abbas Klaten.Method: This study is a case-control study through a quantitative approach and was supported with qualitative data. The research sample is 68 teenage girls of SMP IT PPTQ Ibnu Abbas Klaten who fulfilled the inclusion criteria. The cases groups are female students with low learning achievement, while the control group was female students with high learning achievement. The samples were taken using simple random sampling. Researcher used a structured questionnaire, interview and secondary data to collect the data. The data analysis was using descriptive and inferential analysis including bivariate analysis using chi-square test and multivariate analysis using logistic regression with 95% confidence intervals (CI) and a significance level of p <0.05.Result and Discussion: The bivariate and multivariate analysis showed a significant correlation between primary dysmenorrhea and learning achievement. The possibility of finding girls with primary dysmenorrhea in the group of students who received a low learning achievement is 3 times larger than the group of students who received high learning achievement. Below-average intelligence is greater in the group of low-achieving students than the group of high-achieving students. There is a correlation between the variables of intelligence, stress level and frequency of dysmenorrhea and academic achievement. The variable of absences frequency not related to learning achievement.Conclusion: There is correlation between primary dysmenorrhea and learning achievement (p=0.026). This study indicates that women and their school should pay attention to their menstrual function and dysmenorrhea phenomenon.Keywords: learning achievement, primary dysmenorrhea, teenage, menstrual disorder